Physical consequences of non-Abelian duality in the standard model - Chan, H; Tsou, S (1998)
Possible physical consequences of a recently discovered non-Abelian dual symmetry are explored in the standard model. It is found that both Higgs fields and fermion generations can be assigned a natural place in the dual framework, with Higgs fields appearing as frames (or "N-beins") in internal symmetry space, and generations appearing as spontaneously broken dual color. Fermions then occur in exactly three generations and have a factorizable mass matrix which gives automatically one generation much heavier than the other two. The CKM matrix is the identity at zeroth order, but acquires mixing through higher loop corrections. Preliminary considerations are given to calculating the CKM matrix and lower generation masses. New vector and Higgs bosons are predicted.